OX40 triggering concomitant to IL12-engineered cell vaccine hampers the immunoprevention of HER2/neu-driven mammary carcinogenesis. (3rd August 2018) - Nanni, Patrizia; De Giovanni, Carla; Burocchi, Alessia; Nicoletti, Giordano; Landuzzi, Lorena; Palladini, Arianna; Ianzano, Marianna Lucia; Arioli, Ivano; Colombo, Mario P.; Lollini, Pier-Luigi
ABSTRACT: This study evaluated the effects of combining an OX40 agonistic antibody (aOX40) with a cell vaccine targeting HER2/neu, called "Triplex". Such HER2/neu cell vaccine included two biological adjuvants (interleukin 12 (IL12) and allogeneic histocompatibility antigens) and was previously found able to prevent autochthonous HER2/neu-driven mammary carcinogenesis. Timing of aOX40 administration, concomitantly or after cell vaccination, gave opposite results. Unexpectedly, vaccine efficacy was hampered by concomitant OX40 triggering. Such decreased immunoprevention was likely due to a reduced induction of anti-HER2/neu antibodies and to a higher level of Treg activation. On the contrary, aOX40 administration after the completion of vaccination slightly but significantly increased immunopreventive vaccine efficacy, and led to increased production of GM-CSF and IL10. In conclusion, OX40 triggering can either impair or ameliorate immunoprevention of HER2/neu-driven mammary carcinogenesis depending on the schedule of aOX40 administration.